2021
DOI: 10.3390/su13158373
|View full text |Cite
|
Sign up to set email alerts
|

Neuroeconomic Decisions in Cocoa Producers: Impact of Cooperative Innovation Methodology on Prospecting for Fair Trade Organic Niche as an Incentive for Agricultural Sustainability

Abstract: This article focuses on analyzing the neuroeconomic decisions in cocoa producers and the impact of this methodology on the productivity of fair trade organic cocoa producers on the population of Nuevo Bambamarca, province of Tocache, Peru. The main elements of the methodology are the incentive phase of associativity, the alignment phase to macro trends, the prospecting phase of the country to be exported to, the prospecting phase of the type of niche market, the prospecting phase of fair participation, the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…To predict organizational behavior, it is sufficient to identify the learning process in a hierarchical path from the bottom up with the correlation of holistic integrated innovation competencies of each small producer in each of its microworlds facing individual entrepreneurship decisions developing competencies that would then allow him to make collective decisions at the managerial level in an organization. According to Mavrodiev, P.; Schweitzer (2021) [68] collective wisdom could establish that the average of all opinions is closer to the truth, but groups would make decisions to maintain their initial decision if no more information is available, but if they had more information they could change their initial decision as small cocoa producers who preferred to maintain their status as individual entrepreneurs even when they did not achieve the expected results in Zúñiga (2021) [9].…”
Section: Phases Of the Organizational Memory Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…To predict organizational behavior, it is sufficient to identify the learning process in a hierarchical path from the bottom up with the correlation of holistic integrated innovation competencies of each small producer in each of its microworlds facing individual entrepreneurship decisions developing competencies that would then allow him to make collective decisions at the managerial level in an organization. According to Mavrodiev, P.; Schweitzer (2021) [68] collective wisdom could establish that the average of all opinions is closer to the truth, but groups would make decisions to maintain their initial decision if no more information is available, but if they had more information they could change their initial decision as small cocoa producers who preferred to maintain their status as individual entrepreneurs even when they did not achieve the expected results in Zúñiga (2021) [9].…”
Section: Phases Of the Organizational Memory Methodologymentioning
confidence: 99%
“…When analyzing the results of the behavior of collective entrepreneurship of small producers of alternative organic cocoa crops and fair trade comparing it with the behavior of individual entrepreneurship of small producers, it was identified that productivity was higher in collective entrepreneurship considering that prices were the same in both groups (Zúñiga, 2021) [9].…”
Section: Phases Of the Organizational Memory Methodologymentioning
confidence: 99%
See 3 more Smart Citations